2014
DOI: 10.1111/jeb.12548
|View full text |Cite
|
Sign up to set email alerts
|

The influence of feeding on the evolution of sensory signals: a comparative test of an evolutionary trade‐off between masticatory and sensory functions of skulls in southern African Horseshoe bats (Rhinolophidae)

Abstract: The skulls of animals have to perform many functions. Optimization for one function may mean another function is less optimized, resulting in evolutionary trade-offs. Here, we investigate whether a trade-off exists between the masticatory and sensory functions of animal skulls using echolocating bats as model species. Several species of rhinolophid bats deviate from the allometric relationship between body size and echolocation frequency. Such deviation may be the result of selection for increased bite force, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 73 publications
(134 reference statements)
0
34
0
Order By: Relevance
“…Interestingly, all extant species of carnivorous and animalivorous bats emit echolocation calls nasally, whereas most insectivorous and both piscivorous bat species are oral echolocators. Recent work on a family of nasal echolocating bats (Rhinolophidae) demonstrated trade-offs between masticatory and sensory functions; higher bite forces, a product of a shorter rostrum, are associated with higher echolocation frequencies [76]. Simultaneously, resting frequency and pulse repetition scale negatively with bat size, and pulse duration scales positively with body mass in certain species [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all extant species of carnivorous and animalivorous bats emit echolocation calls nasally, whereas most insectivorous and both piscivorous bat species are oral echolocators. Recent work on a family of nasal echolocating bats (Rhinolophidae) demonstrated trade-offs between masticatory and sensory functions; higher bite forces, a product of a shorter rostrum, are associated with higher echolocation frequencies [76]. Simultaneously, resting frequency and pulse repetition scale negatively with bat size, and pulse duration scales positively with body mass in certain species [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…These adaptive complexes can also include skull shape and size because it houses features for the production and reception of sensory signals while also functioning in handling and mastication of food. This has been evident in both mammals and birds (Freeman & Lemen, 2010;Jacobs, Bastian, & Bam, 2014). Nevertheless, several studies have also implicated drift in the evolution of acoustic signals that are used in reproduction rather than orientation, for example, in Neotropical singing mice (Campbell et al, 2010), anurans (Ohmer, Robertson, & Zamudio, 2009), and in birds (Irwin, Thimgan, & Irwin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…RF of R. clivosus s.l. is almost 40 kHz above that expected based on body mass), which may be because selection increase bite force and then promote a decrease in snout length, and thus could in turn lead to higher frequencies (Jacobs et al ., ). Santana & Lofgren () showed that horseshoe bats in Africa and Mediterranean regions have a proportionally taller skull and a narrower rostrum with a smaller nasal capsule, which may explain partly that several species emit frequencies that are higher than what would be expected based on body size.…”
Section: Discussionmentioning
confidence: 97%
“…The nasal capsules enhance the second harmonic of the echolocation calls by forming part of a frequency-specific impedance matching system during vocalization (Hartley & Suthers, 1988;Pedersen, 1998). Differences in size and shape of the nasal capsules have been found across horseshoe bat species, and have been seen as a cause behind divergences in echolocation frequency among populations within a species (Armstrong & Coles, 2007;Odendaal & Jacobs, 2011) as well as across species (Jacobs et al, 2014). Here, we found that RF was significantly and negatively related to both NSH and PC1 extracted from the measurements of the nasal capsules among horseshoe bats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation